CREATIVE APPROACHES TO DEPICTING HISTORICAL URBAN LANDSCAPES IN CONTEMPORARY UZBEK ART - Madaliyeva Rushana Farhod qizi, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article explores how contemporary Uzbek painters represent historical urban landscapes, focusing on the integration of architectural, cultural, and social elements into visual compositions. The study highlights artistic techniques such as composition, color harmony, perspective, and symbolism, and discusses how these approaches contribute to the preservation of cultural heritage and art education.